2020
DOI: 10.5114/ceh.2019.95115
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for hepatocellular carcinoma recurrence after microwave ablation

Abstract: Aim of the study: Microwave ablation (MWA) for treatment of hepatocellular carcinoma (HCC) is a new promising modality. The prognosis after treatment is mainly linked to the recurrence. We aimed to investigate the predictive value of α-fetoprotein (AFP) score and Aurora B kinase (AURKB) in HCC recurrence after MWA. Material and methods: A cross-sectional study where 25 early-stage HCC patients (Barcelona Clinic Liver Cancer 0/A-B) were treated with MWA. Tumor biopsies were obtained just prior to MWA and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, our PPI network further identified CCNA2 as an up-regulated central gene of HCC, which is consistent with the study of Song et al (26), that is, increased messenger RNA (mRNA) expression of the CCNA2 gene is related to unfavorable RFS and OS in HCC patients. In addition, studies have also shown that AURKB has an important predictive value for the prognosis of HCC (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our PPI network further identified CCNA2 as an up-regulated central gene of HCC, which is consistent with the study of Song et al (26), that is, increased messenger RNA (mRNA) expression of the CCNA2 gene is related to unfavorable RFS and OS in HCC patients. In addition, studies have also shown that AURKB has an important predictive value for the prognosis of HCC (27,28).…”
Section: Discussionmentioning
confidence: 99%